QUALITY AND STABILITY OF SMOKE JERKED DUMBO CATFISH (Clarias gariepinus) IN A DIFFERENT STORAGE SPACE TEMPRATURE - Ilham Azhari Nasution; Syahrul Syahrul; Bustari Hasan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abtracthe aim of the research was to know the quality and stability of a smoked jerked dumbo catfish (clarias gariepinus). The research using an experimental method, making smoked jerked dumbo catfish with 0, 15 and 30 days in a different storage . the research design using a complitely randomized design (CRD), with 3 steps of treatment, those are using 0, 15 and 30 days long in storage space. Organoleptic, chemical analysis and total bacterial colonies are the parameters that must be observe in this case. The experiment result shown that the quality and stability of smoked jerked dumbo catfish (clarias gariepinus) during in storage with room temperature has a real effect to the visual value, smell, texture, taste, water content, ash, protein, fat, and total bacterial colonies test proved 95% convidence level. The best of smoked jerked dumbo catfish result with a different storage temperature was in H0 and H15 with a perfect characteristic, very tidy, interesting and dark brown, typical smell, solid texture, tender, good taste, tasty and chemical quality has qualify to the national standard of indonesia with water content 17%, ash content 0.47%, protein 42.44%, fat 10.88%, and total bacterial colonies are 3.7 x 103 colonies/g and characteristic in H15 has a perfect texture, tidy, the taste is so spesific as smoked meat, solid, tender, tasty, good chemical quality, water content 31.04%, ash content 1.39%, protein, 34.03%, fat 14.31%, with total bacterial colonies are 3.3 x 103 colonies/gKeyword: Smoked Jerked Dumbo Catfish, storage space, room temperature key word: smoked jerked fish, catfish, storage periode, room temperature